Hubungan Indeks Massa Tubuh dengan Kesegaran Jasmani Siswa Kelas IV-V di SD Negeri Purwoyoso 06 - Wildan, Anas Azam; Raharjo, Agus (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the relationship between body mass index and the level of physical fitness of students in grades IV-V at SD Negeri Purwoyoso 06. The type of research used was correlation research with a bivariate correlation research design. The population and sample of this study were students in grades IV – V at SD Negeri Purwoyoso 06 Ngaliyan Semarang City, with a total of 57 students. The sampling technique used the total sampling technique. The results showed that the Body Mass Index of students in grades IV – V at SD Negeri Purwoyoso 06 Semarang City was in the normal category with an average of 19.95. While the level of physical fitness is in the moderate category with an average of 14.60. In conclusion, in this study, there is a relationship between BMI and the level of physical fitness = 0.300 and 0.260 with a Sig. 0.023 <0.05, then is rejected and is accepted, which means that if there is a relationship, the relationship is significant between the independent variables and the dependent variable, with a low correlation. Suggestions in research to maintain eating patterns and often carry out daily activities so as to create a normal body shape and good physical fitness.